2019
DOI: 10.21608/edj.2019.76037
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Assess the Post Operative Pain Intensity Following Non-Surgical Root Canal Treatment and Pulp Revascularization in Mature Necrotic teeth

Abstract: Introduction: Traditionally necrotic permanent teeth are managed through the conventional procedures of root canal treatment which is known to weaken the remaining tooth structure. Regenerative Endodontic Procedures so have emerged as an alternative to the conventional technique Aim of the study: The aim of the present study was to compare the post-operative pain intensity following non-surgical root canal treatment and revascularization procedures in mature necrotic teeth. Materials and methods: Twenty-four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Regarding the incidence and intensity of pain after the revascularization/obturation visit (after the second visit), the pain score of the revascularization group was statistically significantly lower than the endodontic treatment group after 12 h. On the contrary Tawfik et al (2019) showed that pain after revascularization was significantly higher at 6, 12 and 24 h postoperatively when compared to the conventional endodontic treatment, whilst Arslan et al (2019) showed that there was no statistically significant difference regarding the postoperative pain between the revascularization group and the endodontic group in mature necrotic single-rooted teeth.…”
Section: Group Variablementioning
confidence: 89%
“…Regarding the incidence and intensity of pain after the revascularization/obturation visit (after the second visit), the pain score of the revascularization group was statistically significantly lower than the endodontic treatment group after 12 h. On the contrary Tawfik et al (2019) showed that pain after revascularization was significantly higher at 6, 12 and 24 h postoperatively when compared to the conventional endodontic treatment, whilst Arslan et al (2019) showed that there was no statistically significant difference regarding the postoperative pain between the revascularization group and the endodontic group in mature necrotic single-rooted teeth.…”
Section: Group Variablementioning
confidence: 89%
“…Pain levels were higher after 6 hrs as compared to 24 and 48 hrs, that would be related to the triggering of the inflammatory process peri-apically during the endodontic treatment. The polymorphonuclear leukocytes permeate the traumatized site within 6 hours, besides the outpouring of inflammatory mediators (11) .48 hours later, the proliferation stage begins with a lowering in the PMNs counts, and the macrophages penetrate the wound location (11) . Similarly, Pak and White, (12) documented a 40% pain incidence during the first 24 hours that was abruptly reduced after cleaning and shaping throughout the first two days.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the exacerbation or induction of the inflammatory response in the periapical tissues due to endodontic treatment. The polymorphonuclear leukocytes (PMNs) begin to enter the injured site within 6 hours, followed by an increase in the release of inflammatory mediators and neuropeptides ( 44 ). The proliferative process begins after 48 hours, which is characterised by a decrease in the PMNs population, in addition to the macrophages beginning to enter the wound site ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphonuclear leukocytes (PMNs) begin to enter the injured site within 6 hours, followed by an increase in the release of inflammatory mediators and neuropeptides ( 44 ). The proliferative process begins after 48 hours, which is characterised by a decrease in the PMNs population, in addition to the macrophages beginning to enter the wound site ( 44 ). Furthermore, comparable findings were detected in a systematic review conducted by Pak and White (2011) ( 45 ), in which pain incidence was 40% in the first 24 hours and then sharply declined after chemo-mechanical preparation over the first two days.…”
Section: Discussionmentioning
confidence: 99%